ANALISIS POTENSI PENERIMAAN PAJAK PENERANGAN JALAN DI KABUPATEN SIDOARJO - Zakariyah, Eviyanti; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to analyze the potency of highway lighting tax revenue at the district of Sidoarjo during the years of 2009 to 2013. To find out the potency of the revenue and the effectiveness of highway lighting tax a time series research data is required. The research which applies time series will help to know how the performance of highway lighting tax revenue is. This research is a qualitative research, while the data analysis technique applies the percentage descriptive method. The research is conducted at Dinas Pendapatan, Pengelolaan Keuangan dan Aset (DPPKA) Kabupaten Sidoarjo and PT PLN (Persero) Distribusi Jawa Timur Area Pelayanan Sidoarjo. The calculation of the potency of highway lighting tax revenue describes that the determination Determination of the potential for street lighting tax in Sidoarjo is good enough. Realization also has exceeded a predetermined potential. The Industrial electricity tariff class is a class of electricity customers from PT PLN (Persero) which has the largest potency of highway lighting tax revenue when it is compared to the household and business electricity tariff class. The result of the calculation of the effectiveness of highway lighting tax revenue describes that the collection and the management of the highway lighting tax at district of Sidoarjo already quite effectiveness.Keywords: Highway Lighting Tax, Revenue Potency, Realization and Effectiveness.